2017
DOI: 10.1016/j.ajo.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of Optic Nerve Head and Peripapillary Tissues by Horizontal Duction

Abstract: Purpose To ascertain deformation of the optic nerve head (ONH) and peripapillary tissues caused by horizontal duction. Design Prospective, experimental study. Methods Optical coherence tomography of the ONH region was performed in 23 eyes of twelve normal volunteers in central gaze and increasing (10, 20, and 30°) adduction and abduction. Main outcome measures were changes from central gaze in the configuration of the ONH and peripapillary tissues in eccentric gazes. Results Adduction but not abduction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
69
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 49 publications
(76 reference statements)
10
69
1
5
Order By: Relevance
“…Other independent studies also concluded that ONH deformation was more affected by adduction. 13,15 Additionally, a higher ppS stress in adduction also was consistent with a larger optic nerve sheath traction force predicted in this study. We speculated that the overall higher stresses in ppS and higher traction forces in adduction were because of a more elongated optic nerve in adduction than in abduction for the same magnitude of eye rotation.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Other independent studies also concluded that ONH deformation was more affected by adduction. 13,15 Additionally, a higher ppS stress in adduction also was consistent with a larger optic nerve sheath traction force predicted in this study. We speculated that the overall higher stresses in ppS and higher traction forces in adduction were because of a more elongated optic nerve in adduction than in abduction for the same magnitude of eye rotation.…”
Section: Discussionsupporting
confidence: 87%
“…41 The shearing deformation observed in this study (Fig. 2) and other OCT observations [13][14][15] might be able to explain the optic disc rotation about the vertical axis (axis along the superior-inferior direction) observed in myopic eyes. 42 It is plausible that continuous stretching of peripapillary tissues following repeated eye movements might contribute to the development of rotated optic discs and peripapillary zones simultaneously through a tissue remodeling process.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Thyroid eye disease (TED) is an autoimmune disorder where activated orbital fibroblasts 63 differentiate into adipocytes or myofibroblasts and have increased hyaluronan production (1). These 64 processes often involve expansion and infiltration of the orbital fat and the extraocular muscles (2,3). 65…”
mentioning
confidence: 99%